Train Where You Expect to Fight: Why Military Exercises Have Increased in the High North - Duncan Depledge (Scandinavian Journal of Military Studies, 2020)
The new Arctic Military Exercise (ArcMilEx) dataset, which I introduce in this article, demonstrates that since 2006, Western-led military exercises have increased in the ‘High North’ (European Arctic), and that involvement in such exercises is not limited to Arctic states (26 European countries from beyond the Arctic have participated in at least one of these exercises). What the increased number of military exercises shows is that Western states (including both Arctic and non-Arctic countries) are keen to demonstrate that they have the capabilities, competence and resolve to project force in the northern high latitudes to deter potential adversaries. This paper examines the reasons behind this activity. First, it highlights the calls made by small Arctic states, especially Norway and Iceland, for their non-Arctic allies to increase their military presence in the High North. Second, it points to the renewal of NATO’s commitment to deterrence and territorial defence in Europe, including the High North, as it has sought to improve Alliance cohesion and enhance interoperability. Both developments have emerged in response to concerns growing in the West about Russia’s military ambitions in the Arctic, North Atlantic and Europe, especially since President Vladimir Putin’s re-election in 2012. The paper concludes that the material increase in Western military exercises weakens claims that cooperation is the dominant trend in the Arctic and reinforces recent scholarly analyses that paint a more complex picture of the contemporary regional security environment where conflict and cooperation go hand in hand. Using the new ArcMilEx dataset to monitor military exercises in the Arctic (and 'who' is participating in them) is shown to be a valuable barometer of both Arctic and non-Arctic states’ concern about regional stability and security.